The predictive role of peripheral serum inflammatory markers NLR, PLR, and LMR in ulcerative colitis and Crohn’s disease: a systematic review and meta-analysis - Tan, Shufa; Yang, Xiaoqing; Mu, Xiaojing; Liu, Shuang; Wang, Yao; Li, Yuwei; Bian, Yuhong; Xu, Chen (Frontiers in Immunology, 2025)
BackgroundThe neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are peripheral serum markers commonly utilized as cost-effective indicators of inflammation. However, their efficacy as predictors of clinical disease activity in inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), remains uncertain. To address this ambiguity, we conducted a meta-analysis to evaluate the clinical significance of NLR, PLR, and LMR in patients with IBD.MethodsA comprehensive search was conducted in the PubMed, Embase, Web of Science, and Cochrane databases, with the last search date being October 2024. Baseline values of NLR, PLR, and LMR during active and remission phases, as well as moderate and severe conditions, were analyzed as primary endpoints in patients with IBD compared to healthy populations, using risk ratios (WMD) and corresponding 95% confidence interval (CI) estimates.ResultsTwenty-three cohort studies involving 3550 IBD patients and 1010 healthy people were finally included in this meta-analysis. The results of the meta-analysis showed that peripheral serum NLR and PLR were significantly higher in IBD patients than in the healthy population NLR [WMD=1.57,95%CI(1.14,2.01),P<0.001], PLR [WMD=60.66,95%CI(51.68,69.64),P<0.001]; NLR in active versus remission stage of IBD, PLR, LMR had significant differences NLR [WMD=1.50,95%CI(1.23,1.78),P<0.001], PLR [WMD=69.02,95%CI(39.66,98.39,P<0.001], LMR [WMD=-1.14,95%CI(-1.43,-0.86,P<0.001]; IBD active period and remission period NLR, PLR and LMR had significant differences. 0.001]; there were significant differences in NLR and PLR between moderate and severe IBD NLR [WMD=-1.41,95%CI(-2.13,-0.69),P<0.001], PLR [WMD=-112.03,95%CI(-143.87,-80.19),P<0.001]; the diagnostic accuracy of markers in predicting the clinical activity of IBD was relatively good. The diagnostic accuracy of markers in predicting IBD clinical activity was more favorable AUC [ES=0.72,95%CI(0.69,0.75),P<0.001].ConclusionIn patients with IBD, elevated NLR and PLR are associated with increased disease activity and severity in UC and CD. Conversely, an elevated LMR is linked to reduced disease activity in IBD. Based on diagnostic accuracy results, inflammatory markers NLR and PLR serve as effective biomarkers for assessing IBD activity, thereby providing valuable insights for treatment decisions in IBD patients. However, LMR may not be a reliable independent marker due to conflicting or non-significant results. We anticipate that further high-quality prospective studies will validate our findings in the future.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024608118.